1993
DOI: 10.1523/jneurosci.13-03-00941.1993
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 vector-mediated gene transfer of the human nerve growth factor receptor p75hNGFR defines high-affinity NGF binding

Abstract: A series of recombinant herpes simplex virus (HSV-1) vectors have been constructed that encode either the full-length cDNA of the human p75 NGF receptor (p75hNGFR) or truncated forms of the receptor. Infection of cultured fibroblast cells with viral stocks results in abundant expression of all three cDNAs, as detected by affinity cross-linking, immunoblot analysis, and equilibrium binding. Furthermore, viral infection of primary neuronal cultures gives easily detectable p75 expression by immunofluorescence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…It was shown that in mature oligodendrocytes (10) NTR and p140 trkA are expressed on the cell surface, NGF receptor binding affinity is in the picomolar range (35), and NGF signals through p140 trkA leading to cell survival (36). Indeed, in the adult organism, presumptively through coordinated binding to both p75 NTR and p140 trkA , NGF can augment survival of aged neurons (37)(38)(39) as well as the survival of neurons after various injuries like hypoglycemia (40,41), axotomy (42)(43)(44), or exposure to neurotoxic substances (45).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in mature oligodendrocytes (10) NTR and p140 trkA are expressed on the cell surface, NGF receptor binding affinity is in the picomolar range (35), and NGF signals through p140 trkA leading to cell survival (36). Indeed, in the adult organism, presumptively through coordinated binding to both p75 NTR and p140 trkA , NGF can augment survival of aged neurons (37)(38)(39) as well as the survival of neurons after various injuries like hypoglycemia (40,41), axotomy (42)(43)(44), or exposure to neurotoxic substances (45).…”
Section: Discussionmentioning
confidence: 99%
“…NTR undergoes a change in affinity from a Kd of 3 nM to approximately 30 pM upon association with members of the trk tyrosine kinase family of NTRs, presumably by formation of a physical complex Battleman et al, 1993;Benedetti et al, 1993;Barker & Shooter, 1994;Hantzopoulos et al, 1994;Mahadeo et al, 1994;Wolf et al, 1995). The repeat unit 11 of NTR displays features that would indicate a functional role in intersubunit contacts.…”
Section: Versatility Of Modular Architecture and Interactions Betweenmentioning
confidence: 99%
“…Although not accepted by all investigators, NTR interacts with gpl40trk on both sides of the cell membrane to form the highaffinity binding complex (Hempstead et al, 1990;Battleman et al, 1993;Benedetti et al, 1993;Mahadeo et al, 1994;Wolf et al, 1995). Intracellular domain contacts appear to be essential for bringing the two different subunits into the complex, whereas their extracellular domains establish a high-affinity binding site (Wolf et al, 1995).…”
Section: Versatility Of Modular Architecture and Interactions Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, p75 NTR regulates Trk receptor signaling. p75 NTR potentiates NGF activation of TrkA at low ligand concentrations (15,16) and collaborates with TrkA to form high affinity binding sites (17)(18)(19). Furthermore, the signaling pathways initiated by p75 NTR block Trk receptor signaling in certain contexts (20,21) and synergize with Trk receptor signaling in other contexts (22).…”
mentioning
confidence: 99%